PENINGKATAN PENDIDIKAN KARAKTER UNTUK PEMBELAJARAN IPS PADA SISWA SD MELALUI ELECTRONIC WORDLESS PICTURE BOOK - nadhifa; Nida Silma; Pri Nur Wulandari; Tri Suci Ramadhan; Arita Marini (Bajang Institute, 2023)
This study aims to improve character education for social studies learning for elementary school students through the Electronic Wordless Picture Book so that it can be better and more interesting when applied. The method used was library research and data collection was carried out by exploring several journals, books and electronic documents relevant to the study. The results of the study show that the Electronic Wordless Picture Book can improve children's ability to apply various character education within the scope of social sciences in their schools, such as learning to socialize, caring about social and environmental issues, and having a high sense of nationality. Therefore, the Electronic Wordless Picture Book can be used as an interesting learning media and assist teachers in facilitating the learning of social values.